1998
DOI: 10.1002/(sici)1097-4628(19980912)69:11<2271::aid-app20>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Microhardness under strain. III. Microhardness behavior during stress-induced polymorphic transition in blends of poly(butylene terephthalate) and its block copolymers

Abstract: ABSTRACT:The microhardness ( H) technique was recently applied to poly(butylene terephthalate) (PBT) and its multiblock copolymer of poly(ether ester) (PEE) type for examination of the stress-induced polymorphic transition. In the present study, these investigations are extended to blends of PBT and PEE. For this purpose, drawn and annealed with fixed ends at 170ЊC for 6 h in vacuum bristles of PBT-PEE, blends were characterized with respect to their microhardness at various stages of tensile deformation. H wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Stress-induced changes in microhardness measurements have been reported in the literature, and demonstrate that the material hardness decreases with increasing levels of strain [19,29]. However, it is possible to observe a reversal in this trend, depending on the specific polymer.…”
Section: Equationmentioning
confidence: 78%
“…Stress-induced changes in microhardness measurements have been reported in the literature, and demonstrate that the material hardness decreases with increasing levels of strain [19,29]. However, it is possible to observe a reversal in this trend, depending on the specific polymer.…”
Section: Equationmentioning
confidence: 78%
“…It has been shown that the amount of the α and β phases in an isotactic polypropylene (iPP) sample can be successfully distinguished using the microhardness technique . Moreover, microindentation hardness has been applied with success to gain information on the stress-induced polymorphic transition in poly(butylene terephthalate), its block copolymers and blends, and iPP. …”
Section: Introductionmentioning
confidence: 99%
“…We did not observe the mentioned type of cocrystallization, but quite the opposite-formation of continuous crystals comprising two, possibly nonspatially separated (i.e., having common crystal surfaces), crystallographically identical populations of crystallites, differing in size, perfection, origin, and time of appearance [24]. This phenomenon was originally [24] called "partial cocrystallization" and proven by smallangle X-ray scattering (SAXS) [24], DSC [24], and microhardness measurements [32]. Thermograms of the oriented blend show two melting peaks, thus proving that the blend comprises two populations of crystallites, probably the more perfect ones arising from the homopolymer PBT and the less-perfect crystallites made from the PBT blocks of the PEE block copolymer [24].…”
Section: Coexistence Of Two Chemically and Crystallographically Identmentioning
confidence: 79%
“…In the case of the first type of cocrystallization, as reported by Gallagher et al [30] for their system, only a single population of crystallites would exist, and consequently only one polymorphic transition would be found with the progress of deformation. Recently, on the other hand, we described two distinct polymorphic alpha-beta transitions of PBT in the microhardness versus external deformation dependencies for the PBT/PEE blend with lower PBT content [32]. It was concluded that homo-PBT and the PBT segments from PEE segregate in different crystallites [32].…”
Section: Coexistence Of Two Chemically and Crystallographically Identmentioning
confidence: 96%
See 1 more Smart Citation